Protect your self (building self-awareness in preventing lesbian, gay, bisexual, and transgender among elementary school students through counseling) - Amirah Diniaty; Suhertina Suhertina (Journal of Counseling and Educational Technology, 2018)
This research aims to highlight how to prevent LGBT cases that initially occur to primary school student since they are susceptible to be the victims of pedophilia. During this age, they still think concrete, so that they must get proper and correct understanding to protect themselves from LGBT cases. This was an action research by providing counseling services to children: group counseling and information services. The main issue was how to built the students’ awareness in protecting themselves when they interact to the foreigners. This research involved 15 five grade students of Islamic primary school in Pekanbaru and 30 fourth and third grade students of Public Elementry School in Bangkinang. The findings suggest that most students were interested in joining couceling sessions especially in discussing personal issues. The challenge is counselor  needs to provide natural, clear, and understandable information packed with concrete examples and interesting media.